The spectrum of clinical, hormonal and molecular findings in 280 individuals with nonclassical congenital adrenal hyperplasia caused by mutations of the CYP21A2 gene. (3rd August 2014) - Livadas, S.; Dracopoulou, M.; Dastamani, A.; Sertedaki, A.; Maniati‐Christidi, M.; Magiakou, A.‐M.; Kanaka‐Gantenbein, C.; Chrousos, G.P.; Dacou‐Voutetakis, C.
Summary Background Nonclassical congenital adrenal hyperplasia (NC‐CAH) is caused by mutations of the CYP21A2 gene. The clinical manifestations and hormonal derangements of NC‐CAH are quite variable. Objectives (i) To define the phenotype and its relation to genotype according to gender and age and (ii) to evaluate the validity of currently applied hormonal criteria for establishing the diagnosis of NC‐CAH. Patients and Methods The clinical, hormonal and molecular data of 280 subjects (235 female) with NC‐CAH and a median age of 17·6 years were analysed. CYP21A2 genotyping was performed in all subjects. Results The majority of females aged less than 8 years presented with premature pubarche (88·3%), while those older than 8 presented with a polycystic ovary‐like phenotype (63·2%). A total of 7·7% of the females and 51·1% of the males were asymptomatic at the time of diagnosis. In the total group, 50·4% of the subjects were compound heterozygotes for one classical (C) and one nonclassical (NC) mutation, while 46% of the alleles studied carried the p.V281L mutation. Basal 17OHP values were below 6 nm (2 ng/ml) in 2·1% of the subjects with NC‐CAH, but none had peak 17OHP values post‐ACTH lower than 30 nm (10 ng/ml). Conclusions NC‐CAH has a variable phenotype depending on the age, gender and the presence of a classical mutation. A peak cut‐off value of 17OHP post‐ACTH lower than 30 nm excludes the diagnosis of NC‐CAH, whereas basal 17OHP <6 nm may represent a false‐negative result. A significant number of patients harboured a classical mutation, a finding which requires genotyping of the partner for genetic counselling.